2006
DOI: 10.1128/jvi.00287-06
|View full text |Cite|
|
Sign up to set email alerts
|

A trans -Golgi Network Resident Protein, golgin-97, Accumulates in Viral Factories and Incorporates into Virions during Poxvirus Infection

Abstract: Poxviruses are the only DNA viruses known to replicate and assemble in the cytoplasm of infected cells. Poxvirus morphogenesis is a complicated process in which four distinct infectious forms of the virus are produced: intracellular mature virus, intracellular enveloped virus, cell-associated enveloped virus, and extracellular enveloped virus. The source of primary membrane wrapping the intracellular mature virus, the first infectious form, is still unknown. Although the membrane was suggested to originate fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…First and foremost is the origin of inner membrane layers that are present in all NCLDV virions. For Vaccinia membrane biogenesis, ER-Golgi intermediate compartment (ERGIC) membranes were suggested as a source of viral membranes [10], [11], [41], but other studies implied that Vaccinia inner membrane derives from host ER [12], [13], [22], [39]. ER network was also proposed as the source of the ASFV internal membrane [16]–[18], [42].…”
Section: Discussionmentioning
confidence: 99%
“…First and foremost is the origin of inner membrane layers that are present in all NCLDV virions. For Vaccinia membrane biogenesis, ER-Golgi intermediate compartment (ERGIC) membranes were suggested as a source of viral membranes [10], [11], [41], but other studies implied that Vaccinia inner membrane derives from host ER [12], [13], [22], [39]. ER network was also proposed as the source of the ASFV internal membrane [16]–[18], [42].…”
Section: Discussionmentioning
confidence: 99%
“…Golgins such as GM130/golgin-95 (also known as GOLGA2) and p115 (also known as USO1) were found to be components of this matrix, and with their elongated structure, it was suggested that golgins function in the maintenance and establishment of Golgi structure (Slusarewicz et al, 1994;Nakamura et al, 1995;Waters et al, 1992). Knockdown of Golgin-97, Golgin-245 and GCC185 (also known as GOLGA1, GOLGA4 and GCC2, respectively) have been shown to affect the Golgi structure, suggesting a role for golgins in Golgi structure maintenance (Lu et al, 2004;Derby et al, 2007;Alzhanova and Hruby, 2006). Recently it has been reported that efficient stacking occurs in the absence of GRASP65 and/or GRASP55 when either of these two golgins is overexpressed (Lee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The intracellular distribution and dynamic changes of SGIV VP39 in infected cells revealed that VP39 ultimately localizes to the VAS. The major structural proteins are expected to localize to the VAS, as are immature virions and intracellular mature virions (Alzhanova et al 2006;VanSlyke et al 1994). Thus, it is reasonable to infer that the major viral structural protein VP39 is involved in SGIV replication and assembly.…”
mentioning
confidence: 98%